Influenza Vaccine in Children with Cancer Undergoing Chemotherapy - Grace Erdiana; Edi Setiawan Tehuteru (International Medical Journal Corp. Ltd, 2025)
Influenza is a respiratory tract infection caused by a virus that primarily affects children, especially those under 5 years old. Influenza symptoms are generally mild but can worsen in certain conditions such as in immunocompromised patients, including those with cancer. Cancer patients undergoing chemotherapy experience immune system defects, resulting in an inadequate response to infections. It has been reported that children with cancer who contract influenza have longer hospital stays and are at risk of developing pneumonia and respiratory failure. Administration of the influenza vaccine is the most effective prevention to avoid infection and complications from influenza. The inactivated influenza vaccine has been proven safe and can be given to cancer patients undergoing chemotherapy. The challenge in vaccine administration is convincing parents to continue vaccinating their children with cancer.